1993
DOI: 10.1128/jb.175.21.7006-7015.1993
|View full text |Cite
|
Sign up to set email alerts
|

Transcription from two promoters and autoregulation contribute to the control of expression of the Salmonella typhimurium flagellar regulatory gene flgM

Abstract: The flgM gene product has been shown to be a negative regulator of flagellin transcription in Salmonella typhimurium (K. L. Gillen and K. T. Hughes, J. Bacteriol. 173:2301-2310, 6453-6459, 1991; K. Ohnishi, K. Kutsukake, H. Suzuki, and T. Iino, Mol. Microbiol. 6:3149-3157, 1992). Mud-lac fusions to the flgM gene were isolated and used to characterize the regulation of flgM gene expression. Transcription of the flgM gene was decreased more than 30-fold in strains with the flagellar master regulatory genes, flhC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 30 publications
3
57
0
Order By: Relevance
“…More recently it was demonstrated that 28 will transcribe from the promoter regions of the early and middle genes, but the transcriptional start sites differ for FlhDC-dependent class 2 and 28 -dependent class 3 promoters within the middle gene promoter regions (43,63,67,77). A negative regulator of 28 , the FlgM protein (31), is transcribed from a class 2 and a class 3 promoter (32). Among the late genes are those transcribed only from class 3 promoters.…”
Section: Class 2 and Class 3 Promotersmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently it was demonstrated that 28 will transcribe from the promoter regions of the early and middle genes, but the transcriptional start sites differ for FlhDC-dependent class 2 and 28 -dependent class 3 promoters within the middle gene promoter regions (43,63,67,77). A negative regulator of 28 , the FlgM protein (31), is transcribed from a class 2 and a class 3 promoter (32). Among the late genes are those transcribed only from class 3 promoters.…”
Section: Class 2 and Class 3 Promotersmentioning
confidence: 99%
“…The flgN gene is transcribed in the middle class flgAMN operon in addition to the 28 -dependent class 3 flgMN transcript (32,50,72,111). Mutations in flgN result in a poorly motile phenotype with only one or two flagella per cell instead of the normal complement of six to ten (72).…”
Section: Flgn Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…One operon, flhDC, is categorized into class I. The flhDC operon encodes activators required for transcription of the class II operons, including fliA, which encodes the 28 subfamily sigma factor responsible for expression of the class III genes (84,161), and flgM, which encodes the FlgM antisigma factor that regulates activity of FliA (63,162). The remaining class II genes encode proteins responsible for formation of the flagellar basal body and hook apparatus.…”
Section: Fliamentioning
confidence: 99%
“…EGTA (10 mM) was added to the plating medium to limit lysogeny of transductants. Methods for the creation of MudJ transcriptional fusions and Tn10dTc transposon technology were as reported previously (Gillen & Hughes, 1993;Kleckner et al, 1977). For the isolation of loss-of-function mutants following transposition mutagenesis (e.g.…”
Section: Methodsmentioning
confidence: 99%